MENGENAL IKAN-IKAN DANAU SENTANI - Henderite L. Ohee; Henderina J. Keiluhu (JURNAL PENGABDIAN PAPUA, 2018)
Lake Sentani is the biggest lowland lake in Papua and the biggest freshwater fish source in Jayapura. The lake has highest endemism and one of freshwater ecosystem conservation priorities in Papua. Lake organisms consist of water plants, mollusks, crustacea and fish. In Lake Sentani, there are 19 species of fish including endemic, native and anadromous and introduced species. This program aims to deliver knowledge on fish species of Lake Sentani and fish species grouping for elementary school students, grade IV to VI of SD Negeri 5 Puay, Puay Village, East Sentani District, Jayapura. Methods used were seminar, training and practice of fish species grouping, drawing a fish and writing its story. Moreover, pre test and post test consist of questions about Lake Sentani fish and its grouping was deliver to measure the level of knowledge of the students before and after the program. Level of knowledge of students on fish of Lake Sentani was evaluated based on the results of pre test and post test. Student knowledge on Lake Sentani fish species were increasing which show by pre test and post test results. Twelve out of 13 (92%) students showed their post test results were increasing and only one student’s test result was decreasing. Eventhough there are more students with good post test result than those who do not, the level of knowledge on Lake Sentani’s fish and its grouping is not fairly distributed among the students. It is shown by the fact that there are 62% or 8 students  that doing poorly on this test. Therefore, various programmes with various teaching methods for students should be desigend to increase knowledge of students on fish species and its grouping in Lake Sentani. Keywords: fish, fish grouping, Lake Sentani, Puay, students